Inflammatory Responses in α1, 3-Galactosyltransferase Gene-Knockout (GTKO) Porcine Vascular Retransplantation to Cynomolgus Monkeys. (July 2018) - Lee, Eun Mi; Jeong, Jong Cheol; Hurh, Sunghoon; Park, Sohee; Lee, Gwangmin; Yadav, Suchen; Yun, Ik Jin; Min, Sang-Il; Ahn, Curie
Abstract : Introduction: Various pro-inflammatory factors are produced in response to a xenograft. However, it is poorly understood the differences of inflammatory responses by preformed anti-pig antibodies. In this study, we developed the animal model of xenogeneic antibody-mediated rejection of vascular xenografts in sensitized recipients and examined the systemic inflammatory responses. Methods: Cynomolgus monkeys (2.5 4 kg, n=4) received femoral artery grafts from GTKO pig. Immunosuppressive therapy was based on costimulation blockade using anti-CD154 mAb (20 mg/kg). They also received cobra venom factor (0.05 mg/kg), steroid, and tacrolimus. In addition to that, two monkeys received anti-thymocyte globulin (ATG, 20 mg/kg) to minimize T-cell-mediated rejection while allowing the development of donor-specific antibodies. Immunosuppression have been stopped at the time of graft removal (n=4, day 24, 28 or 32). Same immunosuppression protocol was applied for the second vascular transplantation. Whole blood and serum samples were obtained from recipients before and serially after vascular transplantation. They were tested C-reactive protein (C-RP), pro-inflammatory cytokines and chemokines, and blood cell count. In addition, expression of tissue factor (TF) on the transplanted artery was analyzed by immunofluorescence assay. Results: In vascular xenograft recipients, significantly high levels of C-RP were detected in first and second vascular recipients in comparison with before transplantation. The levels of IL-6 and TNF-α were not significantly higher after first vascular transplantation. However, MCP-1 and IL-8 levels were increased after first vascular transplantation. In second xenograft recipients, the level of IL-6, MCP-1, and IL-8 were increased after transplantation, but not TNF-α. Absolute numbers of monocytes and neutrophils were elevated after transplantation. Additionally, peripheral blood leukocytes were increased in the group that ATG was not given after transplantation. TF expressions were increased on the second transplanted artery compare to first transplanted artery. Conclusion: We have developed a model of xenogeneic antibody-mediated rejection in recipients with preformed anti-pig antibodies. The porcine vascular transplantation to Cynomolgus model showed more severe inflammation in second transplanted recipients compare to first transplanted recipients. It means that sensitization to porcine antigens is increased in the vascular retransplanted recipients. This study was supported by the Ministry of Science, ICT & Future Planning (#2014M3A9D3034034).